Designing for privacy in ubiquitous social networking. (6th March 2015) - Sapuppo, Antonio; Figueiras, João
Improving human communication during face–to–face meetings is nowadays possible by transferring online social networking benefits to the physical world. This is enabled by the ubiquitous social networking services that became available by means of wirelessly interconnected smart devices, automatically exchanging personal user data. The main goal of these services is to facilitate the initialisation of relationships between people who do not know each other, but they probably should. Given that sharing of personal information is an intrinsic part of ubiquitous social networking, these services are subject to crucial privacy threats. Inspired by the usability and privacy limitations of existing design solutions, we identify, describe and qualitatively evaluate four drawbacks to be avoided when designing ubiquitous social networking applications. By addressing these drawbacks, services become more functional and more oriented to ensure the end users' privacy, thus contributing to the long–term success of this technology.